One or two Chambers: Does the Senate really serve? Compared perspectives for the chilean constitutional future - Lagos Torres, Alejandro (Derecho Público Iberoamericano, 2021)
The performance of the Senates in bicameral parliaments of the world is analyzed, especially considering the more traditional functions that are attributed to them, to then carry out the same analysis with respect to the Chilean Senate throughout its republican history. It seeks to explain if the Senates are really useful, to finally determine whether in a new Constitution the Chilean Congress should or should not be bicameral.